2019
DOI: 10.3389/fnbot.2019.00057
|View full text |Cite
|
Sign up to set email alerts
|

Stance and Swing Detection Based on the Angular Velocity of Lower Limb Segments During Walking

Abstract: Lower limb exoskeletons require the correct support magnitude and timing to achieve user assistance. This study evaluated whether the sign of the angular velocity of lower limb segments can be used to determine the timing of the stance and the swing phase during walking. We assumed that stance phase is characterized by a positive, swing phase by a negative angular velocity. Thus, the transitions can be used to also identify heel-strike and toe-off. Thirteen subjects without gait impairments walked on a treadmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 55 publications
1
40
0
Order By: Relevance
“…The end of the stride could not be determined by vertical GRF in the same setup (a, b, Fig 1 ) for some of the used strides. For the strides A10, D10, D11, and A11, the end of the stride was therefore determined based on the shank angular velocity zero-crossing, including the removal of the time offset (3% of the gait cycle) based on the findings of [ 26 , 27 ]. As this approach did not work well for some of the subjects for the stair ambulation strides, another approach was required to determine the end of the stride for D3, D4, A6, and A7.…”
Section: Methodsmentioning
confidence: 99%
“…The end of the stride could not be determined by vertical GRF in the same setup (a, b, Fig 1 ) for some of the used strides. For the strides A10, D10, D11, and A11, the end of the stride was therefore determined based on the shank angular velocity zero-crossing, including the removal of the time offset (3% of the gait cycle) based on the findings of [ 26 , 27 ]. As this approach did not work well for some of the subjects for the stair ambulation strides, another approach was required to determine the end of the stride for D3, D4, A6, and A7.…”
Section: Methodsmentioning
confidence: 99%
“…These computation methods are categorized into two main domains. Firstly, the domain based on the threshold method [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ], time-frequency analysis [ 18 , 19 , 20 , 21 ], and peak heuristic algorithms [ 16 , 19 , 22 , 23 , 24 , 25 ], which are also variations of the threshold method. Secondly, Machine Learning (ML) approaches are now among the most popular techniques to detect phases and events with various models such as Hidden Markov Models (HMM) [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ], or several of the latest studies published based on the Artificial Neural Network technique (ANN) [ 35 , 36 , 37 , 38 ], Deep Learning Neural Network (DLNN) [ 39 , 40 , 41 , 42 , 43 ], a Convolutional Neural Network (CNN) [ 44 , 45 , 46 ], or [ 28 ] proposed a hybrid method that combined HMM and Fully connected Neural Networks (FNN).…”
Section: Introductionmentioning
confidence: 99%
“…The models are adopted depending on the type of sensors that are installed for recording the signals of the gait. Nowadays, wearable sensors are widely used for gait phase recognition systems: Wearable force-based measurements [ 9 , 21 , 26 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ], Electromyographic (EMG) sensors [ 55 , 56 ], Inertial Measurement Units (IMUs) [ 9 , 19 , 29 , 41 , 57 , 58 ], and joint angular sensors [ 24 , 59 , 60 , 61 , 62 ] are used specifically for the detection of the gait. The studies showed that the methods that used force-based measurements such as Force Sensing Resistors (FSRs), footswitches, and foot pressure insoles yield the highest precision for detection [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The implementation of the control reference parameter using the MR brake is also not difficult, because the feedback signal can be measured directly by using a rotary encoder. Ankle velocity can also be used to classify the gait phases [36]. This means that only rotary encoder is necessary as the sensor for both classification and control function in future implementation.…”
Section: Discussionmentioning
confidence: 99%